Rehabilitation counselling in physical and mental health - Etherington, Kim (J. Kingsley, 2002)
Individuals experiencing rehabilitation are subject to profound life adjustments, and the contributors to this book explore how the relationship between counsellor and client can be a source of support during that time. Describing pioneering initiatives in a range of rehabilitation settings the authors draw out the historical background and theoretical implications of their work and make recommendations for good practice. Rehabilitation experiences in both physical and psychological health care are described, including those of survivors of strokes, problematic drug or alcohol users, people wh.